The Principle of Effective Demand under Modern Finance: An Exploration in the Traditions of Kalecki and Keynes - Raghavendra, Srinivas (Panoeconomicus, 2018)
The paper explores the principle of effective demand in the context of modern financialization. The traditional “two-sector” model is extended to include banking and finance sectors to examine the implications of the interaction between real and financial sector for effective demand in a closed economy. The analytical framework developed in the paper provides an intuitive understanding of the problem of effective demand in the investment led and consumption led regimes under financialization. It also brings out the underlying dynamics in terms of transfer of profit between the sectors that renders macroeconomic vulnerability in these regimes. Key words: Effective demand, Profit realization, Securitization, Finance sector, Fictitious capital, Investment led regime, Consumption led regime, Underlying assets. JEL: E11, E12, E20, E22, E24, E40, E44. U radu se istražuju principi efektivne tražnje u kontekstu moderne finansijalizacije. Tradicionalni model sa dva-sektora je proširen tako da obuhvata i bankarski i finansijski sektor i ispituje implikacije povezanosti realnog i finansijskog sektora na efektivnu tražnju u zatvorenoj ekonomiji. Analitički okvir razvijen u radu omogućuje intuitivno razumevanje problema efektivne tražnje u investicionom i potrošačkom režimu u okviru finansijalizacije. Takođe, izdvaja se i dinamika u pogledu transfera profita između sektora koji određuju makroekonomsku ranjivost u ovim režimima. Ključne reči: Efektivna tražnja, realizacija profita, sekjuritizacija, finansijski sektor, fiktivni kapital, režim određen investicijama, režim određen potrošnjom, osnovna imovina.